BIOLOGY, HABITS AND GUESTS OF THE ROOT BUG Blissus leucopterus (SAY) (HEMIPTERA: LYGAEIDAE) - VASQUEZ, MARIA NUBIA; SANCHEZ-G., GUILLERMO (Revista Colombiana de Entomología, 1991)
This study was conducted under laboratory and greenhouse conditions at the Entomology Laboratory of "Nataima" Research Center (ICA) at Espinal, Tolima. Results on the life cycle of Blissus leucopterus showed a mean duration of 8,42 and 26.0 days for the egg and nymphal stages respectively. Nymphs passed through five instars. Longevity was higher for adult females - 97.98 days -than for adult males - 91.08 days. The total duration in days, from egg to adult was 35.99 and 31.58 for females and males respectively. The pre-oviposition period was 7.69 days. On average, females oviposited 153.22 eggs with 92% of fertility. One generation averaged 10,82 weeks. Echinochloa colo-num (L.) Link (Graminea) was one of the best hosts for the chinch bug.